Neurovascular Heterodigital Island Flap for Digital Pulp Defect Reconstruction: 58 Case Series - Muhsin Dursun (Acta Medica Alanya)
Aim: Our study aims to report the neurovascular heterodigital island flap reconstruction for finger pulp defects. Patients and Methods: This study included 58 patients presenting to our clinic with pulp defects between 2014 and 2022. The average age of the patients was 26 years (20 - 56 years). Injuries were Allen type 2 for 18 patients, type 3 for 33 patients, and type 4 for 7 patients. Pulp defects were caused by crush injury (n:42) and sharps injury (n:16). Results: None of the flaps administered to the participating patients developed any total loss. Three patients developed partial loss in the distal flap. Six patients were found to have superficial tissue infection. Two patients were found to have hyperpigmentation and hyperesthesia. While one patient with Allen type 3 pulp defect was detected to have 10 degrees of flexion contracture in the distal interphalangeal (DIP) joint and 5 degrees of flexion contracture in the proximal interphalangeal joint, three patients were found to have 5 degrees of flexion contracture only in the DIP joint. The mean static two-point discrimination of the pulp-administered flap was 5.2 mm (3-8 mm) and on the contralateral side was 3 mm. The mean Semmes-Weinstein monofilament test was 3.18 g (2.96 – 4.7 g) in the pulp administered flap and 2.92 g in the contralateral side.Conclusions: Reconstruction of pulp defects with neurovascular heterodigital island flap is a reliable treatment option with satisfactory functional and sensory outcomes.